The relative importance of information events: An ex ante perspective - Iselin, Michael; Van Buskirk, Andrew (Contemporary Accounting Research, 2024)
Abstract We build on recent advances in options pricing research to propose a novel measure of the ex ante relative importance of information events. Our firm‐level measure captures the extent to which investors view an event as important, independent of its realized outcome. We first validate the measure and then demonstrate how it can be used to (1) study heterogeneity across firms in the relative importance of information events; (2) identify firms for which an event was important, even though the realized outcome did not result in a meaningful stock reaction; and (3) examine questions about how the importance of an event impacts firm decisions, where using realized return‐based measures of event importance would result in an endogeneity problem.